Antarctica. (Brussels : Federal science policy office, 2002)
Meiobenthic biodiversity and fluxes within the Antarctic biogeochemicalenvironment -- Structural and ecofuntional biodiversity of the amphipod crustaceanbenthic taxocoenoses in the Southern Ocean -- An integrated approach to assess carbon dynamics in the Southern Ocean -- Southern Ocean global ecosystem response to physical and trophicconstraints -- Study of convective movements in the Southern Ocean -- Mass balance of the Antarctic ice cap (a contribution to EPICA) -- Basal ice from East Antarctica (EPICA) -- Dynamics of the Antarctic ice cap and climate changes (a contribution to EPICA) -- Antarctic shelf-slope dynamics : an innovative geophysical approach
Keywords: Biodiversity -- Antarctica; Ecologie; Ecology -- Antarctica; Poolgebieden